2003
DOI: 10.1097/00000542-200302000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Isoflurane with the Dopamine Transporter

Abstract: The experiments indicate that DAT is trafficked into the cell by isoflurane without changing the total amount of DAT in the striatum. The PET data are consistent with this finding, provided that intracellular DAT acquires a conformation that has low affinity for [18F]FECNT. Thus, [18F]FECNT appears to be an excellent agent for measuring plasma membrane-expressed DAT and evaluating DAT trafficking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 24 publications
1
39
1
1
Order By: Relevance
“…There is much evidence that isoflurane moves the DAT into the cytoplasm so that it inhibits the binding of the DAT-specific tracers [26][27][28][29], which is not concordant with our result. The discordance could be explained by the diversity of the examined tissues (in vitro vs. in vivo studies and Rhesus monkeys vs. rats or mice) or by the different concentrations of isoflurane.…”
Section: Discussioncontrasting
confidence: 83%
“…There is much evidence that isoflurane moves the DAT into the cytoplasm so that it inhibits the binding of the DAT-specific tracers [26][27][28][29], which is not concordant with our result. The discordance could be explained by the diversity of the examined tissues (in vitro vs. in vivo studies and Rhesus monkeys vs. rats or mice) or by the different concentrations of isoflurane.…”
Section: Discussioncontrasting
confidence: 83%
“…Thirdly, too few studies have been carried out on possible effects of anaesthetics on most aspects of CBF, brain metabolism and neurotransmission to provide a solid basis by which to judge the reliability of findings. 17,58 Ideally, confirmatory PET studies could be carried out in unanaesthetized, freely-moving animals, but that goal is currently out of reach in most cases.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…Ether exposure causes a massive expression of fos-like immunoreactivity in specific brain regions, including the basal ganglia and one of its main output nuclei, the substantia nigra pas compacta (Shehab & Julyan, 2002). Isoflurane, however, increases extracellular DA (Adachi et al, 2005), alters DA transporter (DAT) activity (Votaw et al, 2003) and induces hyperlocomotion (Irifune et al, 1998). In addition, studies of pattern generating spinal circuits in vitro explants of fetal or neonatal rat spinal cord have shown that isoflurane disrupts normal patterned activity (e.g., Wong, Sweitzer, Peters & Kendig, 2005).…”
Section: Discussionmentioning
confidence: 99%